Analysis of Breast Aesthetic Revision Procedures after Unilateral Abdominal-based Free-flap Breast Reconstruction: A Single-center Experience with 1251 Patients. Issue 3 (8th March 2023) - Smith, J. Michael; Boukovalas, Stefanos; Chang, Edward I.; Liu, Jun; Selber, Jesse C.; Hanson, Summer E.; Reece, Gregory P.
Abstract : Background: Although autologous free-flap breast reconstruction is the most durable means of reconstruction, it is unclear how many additional operations are needed to optimize the aesthetic outcome of the reconstructed breast. The present study aimed to determine the average number of elective breast revision procedures performed for aesthetic reasons in patients undergoing unilateral autologous breast reconstruction and to analyze variables associated with undergoing additional procedures. Methods: A retrospective review of all unilateral abdominal-based free-flap breast reconstructions performed from 2000 to 2014 was undertaken at a tertiary academic center. Results: Overall, 1251 patients were included in the analysis. The average number of breast revision procedures was 1.1 ± 0.9, and 903 patients (72.2%) underwent at least one revision procedure. Multiple logistic regression analysis demonstrated that younger age, higher body mass index, and prior oncologic surgery on the reconstructed breast were factors associated with increased likelihood of undergoing a revision procedure. The probability of undergoing at least one revision increased by 4% with every 1-unit (kg/m 2 ) increase in a patient's body mass index. Multiple Poisson regression modeling demonstrated that younger age, prior oncologic surgery on the reconstructed breast, and bipedicle flap reconstruction were significant factors associated with undergoing a greater number of revision procedures. Conclusions: Most patients who undergo unilateral autologous breast reconstruction require at least one additional operation to optimize their breast aesthetic results. Young age and obesity increase the likelihood of undergoing additional operations. These findings can aid reconstructive microsurgeons in counseling patients and establishing patient expectations prior to their undergoing microvascular breast reconstruction.